De la Isla al mundo: aproximaciones a la migración cubana contemporánea / From the Island to the World: approaches to contemporary Cuban migration - Marcos Antonio Da Silva (Universidad de La Habana, 2020)
This article analyzes contemporary Cuban international migration, discussing its dynamics and its demographic and economic impact. It discusses the current scenario of international migration, its growth and relationship with globalization. Then, it analyzes recent Latin American migration, presenting its dynamics, profile and the importance of sending remittances to the countries of the region. Finally, discusses contemporary Cuban migration, presenting recent migratory waves and analyzing their dynamics, their distribution, and the population (demographic transition and aging) and economic (remittances) impacts that affect the Caribbean island. Resumen Este artículo analiza la migración internacional cubana contemporánea, discutiendo su dinámica y su impacto demográfico y económico. Con este fin, discute el actual escenario de la migración internacional, su crecimiento y relación com la globalización. Luego, analiza la migración latinoamericana reciente, presentando su dinámica, perfil y la importancia del envío de remesas a los países de la región. Finalmente, discute la migración cubana contemporánea, presentando las olas migratorias recientes y analizando su dinámica, su distribución y los impactos poblacionales (transición demográfica y envejecimiento) y económicos (remesas) que afectan a la isla caribeña.